Biologically Active Phytochemicals: A Brief Appraisal - Mahajan, Ayush; Rana, Pulkit; Singh, Dilpreet; Singh, Kuldeep (Current Traditional Medicine, 2021)
Aim/ Objective: Phytochemicals are considered an ideal candidate for the production of anticancer drugs due to their pleiotropic activity on multi-mode target events. Materials and Methods: Plants are ideal reservoirs for new chemical entities and provide a promising cancer research line. Cancer cells can be formed through different types of mutations, including Point mutation, DNA amplification, chromosomal rearrangement, Epigenetic mutation. Results and Discussion: Products derived from plants are a groundbreaking area because they are eco-friendly, low-cost, Easy, simple, safer, and less toxic compared to other methods of treatment. Vincristine, vinblastine, paclitaxel, camptothecin, cryptolepine, and its analogues, berberine, Antofine, curcumin, ginsenoside, fisetin, chelerythrine, chelidonine, clivorine, clathrodin, dibromophakellstatin, etc are some potential phytochemicals. Conclusion: The review provides in-depth details of structure, properties, mechanism of action and potential anti-cancer activity of phytochemicals derived from plant sources.
Keywords: alkaloid